ANALISIS NILAI MORAL PADA NOVELET “OBAMA OPAPA” KARYA JESSICA ALI - Ulpah Halimatussadiah (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
The novelet "Obama Opapa" by Jessica Ali is one of the literary works that can be used as a source of positive reading for readers. The contents of this novelet are very interesting because the contents of the stories often occur in everyday life. Various moral problems in aspects of life are expressed by the author, especially those that occur in the social environment. The formulation of the research problem is what moral values are contained in the novelet? And what is the description of the research results? Thus the purpose of this study is to identify and describe the moral values contained in Jessica Ali's novelet entitled "Obama Opapa". Qualitative descriptive method is used to analyze moral values in this novelet. Reading, analyzing, and marking fragments are ways to obtain text that can be categorized as moral values. This method is done so that the moral values in the novelet are easily identified, easily understood, and can be applied to daily life by readers. From this research, it is found that the novelet "Obama Opapa" by Jessica Ali contains moral values, including being diligent in worshiping, admitting mistakes, being patient, and being passionate about life, so it is interesting to read by all groups, both adults and adolescents. After getting the results of this research, it is hoped that readers will get the moral values conveyed by the author.